Shelf-Life Extension of Fc-Fused Single Chain Fragment Variable Antibodies by Lyophilization - Schneider, Kai-Thomas; Kirmann, Toni; Wenzel, Esther Veronika; Grosch, Jan-Hendrik; Polten, Saskia; Meier, Doris; Becker, Marlies; Matejtschuk, Paul; Hust, Michael; Russo, Giulio; Dübel, Stefan (Frontiers in Cellular and Infection Microbiology, 2021)
Generation of sequence defined antibodies from universal libraries by phage display has been established over the past three decades as a robust method to cope with the increasing market demand in therapy, diagnostics and research. For applications requiring the bivalent antigen binding and an Fc part for detection, phage display generated single chain Fv (scFv) antibody fragments can rapidly be genetically fused to the Fc moiety of an IgG for the production in eukaryotic cells of antibodies with IgG-like properties. In contrast to conversion of scFv into IgG format, the conversion to scFv-Fc requires only a single cloning step, and provides significantly higher yields in transient cell culture production than IgG. ScFv-Fcs can be effective as neutralizing antibodies in vivo against a panel of pathogens and toxins. However, different scFv fragments are more heterologous in respect of stability than Fab fragments. While some scFv fragments can be made extremely stable, this may change due to few mutations, and is not predictable from the sequence of a newly selected antibody. To mitigate the necessity to assess the stability for every scFv-Fc antibody, we developed a generic lyophilization protocol to improve their shelf life. We compared long-term stability and binding activity of phage display-derived antibodies in the scFv-Fc and IgG format, either stored in liquid or lyophilized state. Conversion of scFv-Fcs into the full IgG format reduced protein degradation and aggregation, but in some cases compromised binding activity. Comparably to IgG conversion, lyophilization of scFv-Fc resulted in the preservation of the antibodies’ initial properties after storage, without any drop in affinity for any of the tested antibody clones.